Observed changes in cardiovascular risk factors among high-risk middle-aged men who received lifestyle counselling: a 5-year follow-up - Reijo Siren; Johan G. Eriksson; Hannu Vanhanen (Taylor & Francis Group, 2016)
Objective: To examine the long-term impact of health counselling among middle-aged men at high risk of CVD. Design: An observational study with a 5-year follow-up. Setting and intervention: All men aged 40 years in Helsinki have been invited to a visit to evaluate CVD risk from 2006 onwards. A modified version of the North Karelia project risk tool (CVD risk score) served to assess the risk. High-risk men received lifestyle counselling based on their individual risk profile in 2006 and were invited to a follow-up visit in 2011. Subjects: Of the 389 originally high-risk men, 159 participated in the follow-up visits in 2011. Based on their follow-up in relation the further risk communication, we divided the participants into three groups: primary health care, occupational health care and no control visits. Main outcome measures: Lifestyle and CVD risk score change. Results: All groups showed improvements in lifestyles. The CVD risk score decreased the most in the group that continued the risk communication visits in their primary health care centre (6.1 to 4.8 [95% CI −1.6 to −0.6]) compared to those who continued risk communication visits in their occupational health care (6.0 to 5.4 [95% CI −1.3 to 0.3]), and to those with no risk communication visits (6.0 to 5.9 [95% CI −0.5 to 0.4]). Conclusions: These findings indicate that individualized lifestyle counselling improves health behaviour and reduces total CVD risk among middle-aged men at high risk of CVD. Sustained improvement in risk factor status requires ongoing risk communication with health care providers.KEY POINTS Studies of short duration have shown that lifestyle changes reduce the risk of cardiovascular disease among high-risk individuals. Sustaining these lifestyle changes and maintaining the lower disease risk attained can prove challenging. Cardiovascular disease (CVD) risk assessment and individualized health counselling for high-risk men, when implemented in primary health care, have the potential to initiate lifestyle changes that support risk reduction. Attaining a sustainable reduction in CVD risk requires a willingness to engage in risk-related communication from both health care providers and the individual at high risk.